Thermo- and pH-sensitive hydrogels functionalized with thiol groups. (February 2015) - Montero-Rama, María Pilar; Liras, Marta; García, Olga; Quijada-Garrido, Isabel
Graphical abstract: Highlights: Synthesis of thiolated hydrogels by free radical polymerization is reported. A new methacrylic monomer (AcSEMA) with thiol protected group was used. Thermo-responsive polymers were obtained by copolymerization with MEO2 MA. After deprotection of thiol groups polymers also showed remarkable pH sensitivity. Abstract: Tacking into account the great potential of hydrogels bearing thiol functionalities, in this work we report the synthesis of thiolated hydrogels by free radical polymerization of (i) a thermo-responsive monomer, 2-(2-methoxyethoxy)ethyl methacrylate (MEO2 MA); (ii) a lower ratio of a monomer having protected thiol group, 2-(acetylthio)ethyl methacrylate (AcSEMA) and (iii) a small proportion of tetraethylene glycol dimethacrylate (TEGDMA) as crosslinker. Subsequently, deprotection of thioacetate groups, by incubating the samples in basic solutions, allows obtaining hydrogels with free thiol groups. After this treatment, the pH dependence of the thiol–thiolate equilibrium makes the thermal response of novel P(MEO2 MA- co -SEMA) strongly modulated by the pH.